Evaluation of Risk in the Development of Pressure-Caused Tissue Lesion in Icu Patients - Correia, Jefferson Nery (2010)
Pressure-caused tissue lesion (PTL) is an issue of great importance especially in Intensive Care Units (ICUs). In fact, it frequently becomes somewhat serious with a high impact on the patient’s recovery. An evaluation of risks is thus necessary to minimize damages done and to make use of such tools, as the Waterlow scale, to help the nursing team in the prevention of the occurrence. Current investigation evaluates the risk of developing PTL in 15 over-18-year-old ICU patients during a period of 64 days, hospitalized for more than 24h in ICUs. Data show a large number of patients who developed PTL, coupled to the factors which contributed towards such a situation. Classified according to lesion degree, 9 (60%) patients developed PTL and indicated the importance of a plan to take care of these lesions in the ICU. Nursing care should be systemized and directly linked to preventive care with regard to PTL.